KEPUASAN WISATAWAN TERHADAP PENDAPATAN EKONOMI DI INDONESIA DENGAN MEDIASI INFRASTRUKTUR - Anggi Oktawiranti; Saida Zainurossalamia Za, Fahrizal Anwar, Dedi Djalipa, Abdul Rauf (CV. Adiba Aisha Amira, 2024)
This study investigates the relationship between traveller satisfaction, economic income, and perceived infrastructure quality in the context of Indonesian tourism. A quantitative approach, using structural equation modelling (SEM), was used to analyse data collected from 110 tourists through the survey method. The results show a significant positive relationship between tourist satisfaction and economic income, as well as between tourist satisfaction and perceived infrastructure quality. In addition, perceived infrastructure quality was found to partially mediate the relationship between economic income and tourist satisfaction. These findings underscore the important role of infrastructure development in enhancing the tourist experience and driving economic benefits in the tourism sector. The implications of these findings for tourism management and destination development in Indonesia are discussed, along with suggestions for future research directions.